2013
DOI: 10.5114/aoms.2013.34560
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome prevalence according to ATP III and IDF criteria and related factors in Turkish adults

Abstract: IntroductionThe aim of this study is to investigate the prevalence of metabolic syndrome (MS) and its components according to Adult Treatment Panel III (ATP III) and International Diabetes Federation (IDF) criteria and the risk factors affecting MS. Metabolic syndrome prevalence was evaluated according to certain quintet age groups, altitude, location and demographic features.Material and methodsThis study was a cross-sectional survey conducted in 24 provinces from the 7 regions of Turkey. A total of 4309 adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
57
3
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 41 publications
12
57
3
4
Order By: Relevance
“…A recent study conducted with Turkish adults demonstrated that the MS prevalence can vary between 36.6 and 44.0%. [3,14] In light of this information, it is important to inform patients fully and correctly after surgery to prevent recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study conducted with Turkish adults demonstrated that the MS prevalence can vary between 36.6 and 44.0%. [3,14] In light of this information, it is important to inform patients fully and correctly after surgery to prevent recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the data, it is important to take into account the contribution of these two factors in the high recurrence of CTS that they developed. [14] To prevent recurrence after CTS surgery, important interventions, including hand-wrist exercises, taking frequent rest breaks and using a splint to hold the wrist and the hand straight in the appropriate position, should be employed. [14] Additionally, as the number of patients with MS is currently increasing, it is also important that hyperglycemia, hyperlipidemia and obesity are controlled to prevent recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While 40% of women are over-weighted in the world, 29.3% of the women are over-weighed and 24.5% are obese in Turkey [6,7]. Studies carried out on this topic have demonstrated in Turkish women that the reduced physical activity, higher birth rate, longer lactation periods, accompanying diabetes and hypertension, lower income and education levels have significantly influenced the obesity [8,9]. However, over weight gained during pre-and-peri-gestational periods in women is one of the leading causes of obesity seen [10].…”
mentioning
confidence: 99%
“…Do observado, nota-se que a prevalência de SM no Brasil não está muito diferente da observada nos EUA (22,9%) (14) . O mesmo pode ser dito em relação aos paises europeus: Portugal (27,56%) (15) , Espanha (26,6%) (16) , França 25% homens e 15,3% mulheres (17) , Italia 28% homens e 26% em mulheres (13) Maiores prevalências foram encontradas na Asia tais como a China (33,9%) e Turquia 36,6% (18) e em alguns países latinoamericanos como Colômbia (34,8%) (19) e Venezuela (35,3%) (20). Desta forma, fica evidente que a SM é uma condição clínica muito comum em todo o Mundo, sendo este um dos motivos pelos quais devemos explorar o real impacto da SM no contexto de suas consequências cardiovasculares.…”
Section: Prevalência Da Smunclassified